(untitled) (The International Journal for Scientific Research, 2024)
This study aimed to identify the attitudes trends of the Sudanese elite, consisting of academics, media Professionals, Politicians and opinion leaders, towards News websites coverage of the Sudanese war which greatly affected Sudanese society with all its components. It turned the residents of the capital city Khartoum and some states into internally displeased People and refugees in neighboring countries. And the media, especially electronic platforms played an important role in following up and disseminating information and events related to this war. The study relied on the survey method using a questionnaire tool that was applied to the study population using a purposive sampling method, the number of which was (165) items. The study reached the following results: - Al Arabia News sites come first on the sites followed by the Sudanese elites followed by Sudanese sites then international sites. - The study recommended the necessity of the News websites playing their active role during crises spreading awareness and interest in the good handling of crises and conflicts in Society, and upholding the values of accuracy, neutrality and credibility in order to gain the public’s trust and ensure its interaction.